83=6(4-8y)+5(9+11y)

Simple and best practice solution for 83=6(4-8y)+5(9+11y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 83=6(4-8y)+5(9+11y) equation:



83=6(4-8y)+5(9+11y)
We move all terms to the left:
83-(6(4-8y)+5(9+11y))=0
We add all the numbers together, and all the variables
-(6(-8y+4)+5(11y+9))+83=0
We calculate terms in parentheses: -(6(-8y+4)+5(11y+9)), so:
6(-8y+4)+5(11y+9)
We multiply parentheses
-48y+55y+24+45
We add all the numbers together, and all the variables
7y+69
Back to the equation:
-(7y+69)
We get rid of parentheses
-7y-69+83=0
We add all the numbers together, and all the variables
-7y+14=0
We move all terms containing y to the left, all other terms to the right
-7y=-14
y=-14/-7
y=+2

See similar equations:

| 2/3d=1415 | | 44+44+44+x=180 | | 4x+21=7(x+8) | | n*5=8 | | x−2−2=4 | | 2x-6=3x+1=x-7 | | 4p−7=−75 | | 8. 3(3x+2)-(2x-8)=7^2+1 | | 4(9k-5)=32 | | 4×n=30 | | 195=-w+1 | | 9(f-91)=36 | | 44*3+x=180 | | 4=k+2 | | 170=30t+50 | | 32-8x=-5+5(1-8x) | | 4(-4-2r)-5(-4r+5)=-65 | | 0.5(2x-8)=3(x-5)+7 | | 3x=15=2(x+)+x+11 | | 3=b/8 | | -5u+13u-(-16)-(-14)=10 | | s+33=–2 | | 234-u=55 | | 5-9s=-8s | | 9d+2d+3d-6-5d=0 | | y/4+22=42 | | (6x-5)×(2x+5)=0 | | 10.5+2x=15 | | 315=-5(1+8k) | | 100n=-500 | | -11+5=-2(x+2) | | –9+x=–1 |

Equations solver categories